Liver transplantation from brain‐dead donors on mechanical circulatory support: a systematic review of the literature. (28th October 2020) - De Carlis, Riccardo; Buscemi, Vincenzo; Checchini, Giuliana; Frassoni, Samuele; Bagnardi, Vincenzo; Pagnanelli, Michele; Lauterio, Andrea; De Carlis, Luciano
Summary: Mechanical circulatory support (MCS) refers to a range of rescue devices to assist circulation for the treatment of heart failure, including venoarterial extracorporeal membrane oxygenation (VA‐ECMO) and ventricular assist devices (VADs). This review aims at evaluating the transplant outcome of the livers procured from brain‐dead donors on MCS, who are currently considered as having extended criteria. We identified 22 records (17 on VA‐ECMO and 5 on VADs), most of which (68.2%) were case reports. We performed a meta‐analysis only when the outcome was reported homogeneously among studies; otherwise, we illustrated the results with narrative synthesis. A total of 156 liver transplants (LTs) have been reported, where VA‐ECMO was initiated in the donor with resuscitative intent or as a bridge to donation. Early graft survival approached 100% in most studies. The pooled rate of primary nonfunction was 1% (95% CI: 0–3%). Only three successful LTs from VAD donors have been reported. Particular attention should be paid to cardiological history, biochemical tests, and imaging, as well as MCS parameters, to determine graft eligibility for transplantation. Although further analysis is needed in this field, the results of this review advocate a more systematic consideration of brain‐dead patients on MCS as potential liver donors.